Differential contribution of TRPM4 and TRPM5 nonselective cation channels to the slow afterdepolarization in mouse prefrontal cortex neurons - Lei, Ya-Ting; Thuault, Sebastien J.; Launay, Pierre; Margolskee, Robert F.; Kandel, Eric R.; Siegelbaum, Steven A. (Frontiers in Cellular Neuroscience, 2014)
In certain neurons from different brain regions, a brief burst of action potentials can activate a slow afterdepolarization (sADP) in the presence of muscarinic acetylcholine receptor agonists. The sADP, if suprathreshold, can contribute to persistent non-accommodating firing in some of these neurons. Previous studies have characterized a Ca2+-activated non-selective cation (CAN) current (ICAN) that is thought to underlie the sADP. ICAN depends on muscarinic receptor stimulation and exhibits a dependence on neuronal activity, membrane depolarization and Ca2+-influx similar to that observed for the sADP. Despite the widespread occurrence of sADPs in neurons throughout the brain, the molecular identity of the ion channels underlying these events, as well as ICAN, remains uncertain. Here we used a combination of genetic, pharmacological and electrophysiological approaches to characterize the molecular mechanisms underlying the muscarinic receptor-dependent sADP in layer 5 pyramidal neurons of mouse prefrontal cortex. First, we confirmed that in the presence of the cholinergic agonist carbachol a brief burst of action potentials triggers a prominent sADP in these neurons. Second, we confirmed that this sADP requires activation of a PLC signaling cascade and intracellular calcium signaling. Third, we obtained direct evidence that the transient receptor potential melastatin 5 channel (TRPM5), which is thought to function as a CAN channel in non-neural cells, contributes importantly to the sADP in the layer 5 neurons. In contrast, the closely related TRPM4 channel may play only a minor role in the sADP.